2009
DOI: 10.1111/j.1365-2826.2008.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Action: Nongenomic Modulation of Neuronal Excitability in the Hippocampus

Abstract: Years of effort have failed to establish a generally-accepted mechanism of thyroid hormone (TH) action in the mature brain. Recently, both morphological and pharmacological evidence have supported a direct neuroactive role for the hormone and its triiodinated metabolites. However, no direct physiological validation has been available. We now describe electrophysiological studies in vivo in which we observed that local thyroxine (T4) administration promptly inhibited field excitatory postsynaptic potentials rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 40 publications
1
27
1
Order By: Relevance
“…In parallel with our findings, it was reported that the efficacy of LTP induction was significantly attenuated in T3-treated rats, indicating that neonatal hyperthyroidism disturbs LTP in the DG of the hippocampal formation [36]. Furthermore, local T4 microinjection in the DG in normothyroid and propylthiouracil-treated rats produced an immediate and long-lasting decrease in the PS amplitude recorded from the DG following stimulation of the medial perforant pathway [51]. Interestingly, depressed I/O relationships [42,44] and impaired LTP [42,44] were also pronounced in hypothyroid rats.…”
Section: Discussionsupporting
confidence: 72%
“…In parallel with our findings, it was reported that the efficacy of LTP induction was significantly attenuated in T3-treated rats, indicating that neonatal hyperthyroidism disturbs LTP in the DG of the hippocampal formation [36]. Furthermore, local T4 microinjection in the DG in normothyroid and propylthiouracil-treated rats produced an immediate and long-lasting decrease in the PS amplitude recorded from the DG following stimulation of the medial perforant pathway [51]. Interestingly, depressed I/O relationships [42,44] and impaired LTP [42,44] were also pronounced in hypothyroid rats.…”
Section: Discussionsupporting
confidence: 72%
“…Our view of what defines the properties of a neuromodulator has recently undergone a major expansion to include molecules like oxide gases, endocanabinoids, hydrogen sulfides, thyroxine, and steroids (Balthazart and Ball, 2006; Caria et al, 2009; Saldanha et al, 2011; Snyder, 2009). For example, nitric oxide appears to act as a stabilizing neuromodulator in the control of multiple movements patterned by a gut CPG in a mollusc (Dyakonova and Dyakonova, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their somewhat peculiar chemistry, most of these nonclassical modulators are not packaged into vesicles for conventional release by neurons, and their release properties and interactions can be comparatively complex (e.g., Boychuk et al, 2013; Huang and Woolley, 2012). Thyroxine itself may share similarities with steroids in terms of ‘synaptocrine’ signaling in the brain, including nongenomic effects (Caria et al, 2009; Davis et al, 2007), a distribution of bouton-like beads along fibers coursing through cortex (Rozanov and Dratman, 1996), and a hypothesized role as neurotransmitters (Dratman and Gordon, 1996; Greenberg et al, 2006). Our understanding of the group of molecules that can modulate neural circuits is now expanding, which illuminates the flexibility afforded to neural circuits to respond to varying internal and external states and generate many flexible outputs.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of T1AM to the locus coeruleus (LC) resulted in an increase in firing of a subset of neurons (Dhillo et al, 2009; Gompf et al, 2010). In contrast, hippocampal cells showed a rapid decrease in excitability upon local administration of T4 in anesthetized rats (Caria et al, 2009). Administration of norepinephrine and norepinephrine agonists to the preoptic region rapidly decreased EEG-defined sleep (Mohan Kumar et al, 1986; Ramesh and Kumar, 1998; Ramesh et al, 1995).…”
Section: Introductionmentioning
confidence: 99%